Exploring Gender Differences in Shaping Total Tourism Experience Quality among Eco-Tourists - Janiffa Saidon; Nurul Ainun Ahmad Atory; Hairulnizam Hashim; Rosidah Musa; Mohd Khalid Mohd Abas; Liatul Izian Ali Husin; Ahmad Nizam Mohd Yusof; Farez Adry Murad (Information Management and Business Review, 2024)
This research explored the role of gender as a moderating effect on the relationship between factors affecting ecotourism experiential value. Previous studies have investigated tourist satisfaction; however, the role of gender towards the experiential value remains unclear. More importantly, the tourist’s actual behavior at a destination is a critical determinant factor of tourist loyalty compared to the perception.  Accordingly, the purpose of this study was to explore the role of gender in the relationship between factors influencing the Ecotourist Experiential Value on Actual Tourist Behaviour. More specifically, this study delved into the consequences of destination experience (i.e. attachment and advocate) and investigated the influence of Ecotourist Experiential Value on Actual Behaviour between genders. A survey was conducted among the Taman Negara patrons in Malaysia. The research model was tested and confirmed with 243 tourists. The data was analyzed using Smart Partial Least Squares which is the variance-based structural equation modelling. The results evoked from the survey indicate that aesthetics is very much important as the influential factors towards positive total experience quality among male compared to female. In contrast, Customer Return on Investment becomes the main concern of female tourists towards Total Experience Quality as compared to male tourists. In light of the major finding, this study accentuates the importance of understanding gender behavior to provide valuable insights for destination marketers to establish positioning plans for the tourism industry.